Contexts of violence victimization and service-seeking among Latino/a/x immigrant adults in Maryland and the District of Columbia: A qualitative study - K.G. Bevilacqua; S. Arciniegas; K. Page; A.K. Steinberg; J. Stellmann; A. Flores-Miller; A.L. Wirtz (Elsevier, 2023)
In the United States (US), Latino/a/x immigrants are particularly vulnerable to discrimination and violence, which are associated with a host of negative physical and mental health consequences. Despite this, Latino/a/x immigrants may have limited access to resources and services to prevent and address its consequences. In-depth interviews (n = 17) and one focus group discussion (n = 5) were conducted among a maximum variation sample of adult Latino/a/x immigrants living in Maryland and the District of Columbia, following semi-structured interview guides to explore experiences of discrimination and violence, their impact on health, and barriers and facilitators to help-seeking. Experiences of discrimination and violence victimization were diverse in type and severity. Many women and one gender non-binary participant described experiences of intimate partner violence as well workplace violence. Men frequently described violence that occurred in public and in the workplace. Nearly all participants reported workplace discrimination. Lack of legal documentation, experiences of impunity in country of origin, and lack of knowledge of the US legal system presented barriers, while peers, social groups, and bystanders facilitated violence reporting and help-seeking. Results highlight clear opportunities to prevent and respond to violence through improved availability and accessibility of information, as well as expansion or adaptation of existing services across sectors.